Tarif Rumah Sakit dengan Tarif INA-CBGs Pasien Rawat Inap - Agiwahyuanto, Faik; Widianawati, Evina; Wulan, Widya Ratna; Putri, Rizqi Basuki (HIGEIA (Journal of Public Health Research and Development), 2020)
Endemic diseases which have quite a high prevalence are cases of DHF. In Indonesia alone DHF numbered 68,407 cases in 2017. The average DHF patient in the RSUD K.R.Tong Wongsonegoro Semarang City was 5.45%. The aim of the study was to analyze differences in hospital rates with INA-CBGs rates in inpatients of DHF cases in the RSUD K.R.T. Wongsonegoro Semarang City in 2018. The type of this research is descriptive analysis, researcher describes difference in hospital tariffs with the rates of INA-CBGs in the RSUD K.R.T. Wongsonegoro, Semarang City. The method used is observation on the index of DHF cases. The subjects in this study were 73 respondents and data analyze using univariate. The results showed that the length of stay and severity level can affect the variation of hospital rates, but the INA-CBGs rate results will remain the same according to the treatment class and severity level even though hospital rates vary. With the difference in higher hospital rates, the management section coordinates the hospital tariff setting and the hospital organization section proposes to increase the INA-CBGs rate to BPJS.